2020
DOI: 10.1002/admi.201901632
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized TiCu/Ti‐Cu‐N‐Coated 3D‐Printed Porous Ti6Al4V Scaffold Promotes Bone Regeneration through BMSC Recruitment

Abstract: Ti6Al4V scaffolds have high strength and corrosion resistance. 3D printing technology can optimize the pore structure of Ti6Al4V scaffolds, promoting bone tissue growth into the scaffolds to form firm osseointegrations. However, Ti6Al4V lacks biological activity. This defect can be overcome through surface modifications. Arc ion plating is employed to prepare titanium copper/titanium copper nitride (TiCu/Ti‐Cu‐N) multilayer coating, which is applied to 3D‐printed porous Ti6Al4V scaffolds by selective laser mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The following outcome ranges do not include values reported for treated pTi or values determined with gap implant fits, which were not representative of the FCD models. For rabbit studies, reported BI ranged from 5.73–36.5% (two reports were excluded due to uncertainty regarding the BI calculation method 37,38 ), BIC ranged from 16.3–59.7%, BV/TV ranged from 4.4–61.1%, bone volume ranged from 5.62–63.3 mm 3 , maximum push‐out force ranged from 46.6–495.9 N, and interfacial strength ranged from 2.84–20.0 MPa. For sheep studies, BI ranged from 3.29–53.4%, BIC ranged from 9.8–56.6%, BV/TV ranged from 5.22–6.27% (values from one study only), maximum push‐out force ranged from 1457–3092 N, and interfacial strength ranged from 5.8–7.5 MPa (values from one study only).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following outcome ranges do not include values reported for treated pTi or values determined with gap implant fits, which were not representative of the FCD models. For rabbit studies, reported BI ranged from 5.73–36.5% (two reports were excluded due to uncertainty regarding the BI calculation method 37,38 ), BIC ranged from 16.3–59.7%, BV/TV ranged from 4.4–61.1%, bone volume ranged from 5.62–63.3 mm 3 , maximum push‐out force ranged from 46.6–495.9 N, and interfacial strength ranged from 2.84–20.0 MPa. For sheep studies, BI ranged from 3.29–53.4%, BIC ranged from 9.8–56.6%, BV/TV ranged from 5.22–6.27% (values from one study only), maximum push‐out force ranged from 1457–3092 N, and interfacial strength ranged from 5.8–7.5 MPa (values from one study only).…”
Section: Resultsmentioning
confidence: 99%
“…While some used single stains popular for bone visualization, 86,97 many others used counterstaining to quantify mature bone, immature bone, or fibrous tissue growth, 56,66 providing useful insight for 3DP Ti osteogenesis. For example, a triple staining method used by Guo et al revealed that copper and copper nitride coatings for 3DP pTi led to greater bone formation via endochondral ossification, 37 while a study by Lv et al used yellow Microfil labeling along with staining to confirm that greater osteogenesis for BMP‐ and VEGF‐loaded 3DP pTi was due to increased vascularization 51 . In addition to tissue staining, numerous studies used fluorochrome labeling with timed injections of tetracycline, calcein green, alizarin red, and/or xylenol orange to visualize bone remodeling over time.…”
Section: Discussionmentioning
confidence: 99%
“…Cu has been shown to be a multi-functional agent that not only increases angiogenesis and osteogenesis, but also inhibits osteoclastogenesis and displays broad-spectrum antibacterial properties [ 9 , 11 ]. Numerous researches have demonstrated that Cu incorporated into a variety of biomaterials would promote their bioactivities [ 8–10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cu ions released from Cu-containing materials are involved in regulating the cellular activities and inhibiting growth of bacteria. The previous studies indicated that the addition of Cu in Ti6Al4V alloys would decrease inflammatory responses, and enhance blood vessel formation and bone regeneration due to the sustained release of Cu ions [ 11–14 ]. When considering the complexity of oral microenvironments, further investigation of Cu-bearing Ti6Al4V alloy on osteoporotic macrophages in infectious microenvironments is required.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D printing machines, based on the stimulation used for integrating matter, can be categorized into (1) laser-based 3D printing technologies which operate using laser stimulation to bond either material powders or fluid medium; (2) extrusion-based 3D printing technologies which extrude molten materials that either cool and physically bond or are further solidified by UV stimulation, and (3) ink-based 3D printing technologies which print liquid or aerosol chemical binders to chemically bond the material powders together. Laser-based technologies include stereolithography (SLA) [118][119][120][121][122][123][124][125][126][127][128][129][130], selective laser sintering (SLS) [131][132][133][134][135][136], electron beam melting (EBM) [137][138][139], LENS [140], SLM [39,[141][142][143][144][145][146][147][148][149], and two-photon polymerization (2PP) [150,151]. Extrusionbased technologies include fused deposition modeling (FDM) [152], and material jetting (MJ) [96].…”
Section: D Printing Technologies Based On Stimulation Usedmentioning
confidence: 99%